(untitled) (Research, Society and Development, 2022)
Cleft lip and palate is one of the most common congenital facial malformations and has a multifactorial etiology. Such comorbidity affects not only the organic and anatomical characteristics, but also the psychological and social aspects. Operation Smile works with the aim of contributing, especially among the most needy population, to multifactorial treatment, aiming at well-being in all aspects of human life. The objective of this study was to report the case of a patient with cleft lip and palate (CLP), born from a twin pregnancy with a twin without the deformity, clinically and surgically followed up by Operation Smile Brazil since childhood, in order to demonstrate and analyze the psychosocial aspects shaped by living with the deformity at different stages of his life, taking into account, mainly, the treatment offered and the family relationship, these factors being indispensable, not only during his growth and development, but also in his social and professional insertion. during adult life. Emphasizing the evolution of a child completely introverted by the stigmas associated with the deformity to a teenager and later a young woman increasingly communicative and socially related as the multiprofessional treatment was applied, in parallel with the support and family care always present in her life, highlighting how important the work of Operation Smile is to society.